The Implementation of KWL Strategy in EFL Students’ Reading Comprehension - Krismalita Sekar Diasti; Cecilia Titiek Murniati; Heny Hartono (JET (Journal of English Teaching), 2023)
Reading is one of the fundamental aspects underlying students’ achievement yet becomes an activity abstained by students. In fact, EFL learners demand more enjoyable and diverse reading activities. Most EFL students perceive that they are continuously exposed to prevalent reading activities. This qualitative study aims to scrutinize the implementation of KWL strategy in EFL reading comprehension. To answer the research question, twelve higher students of the English department were invited as the participants to be interviewed. The findings reflected that EFL learners encountered reading challenges related to vocabulary, reading comprehension, and attention span. However, KWL strategy assisted them, particularly in setting goal, monitoring reading process, and evaluating reading activity.